APPLICATION AND USE OF AI (ARTIFICIAL INTELLIGENCE) IN MEDICINE - Tukhtakhodjaeva , Feruza Shamansurovna; Murodullayev , Mironshokh Nodirbek o‘g‘li; Khayitova, Iroda Ilhomovna (Educational Research in Universal Sciences, 2023)
Artificial Intelligence (AI) has emerged as a transformative force in the field of medicine, revolutionizing how healthcare is delivered, from diagnosis to treatment and beyond. This comprehensive article delves into the multifaceted applications and profound impact of AI in the medical domain. It traces the history and evolution of AI in medicine, exploring the various types of AI technologies employed, including machine learning, natural language processing, and robotics.